Pemberdayaan Guru, Wali Murid, dan Kader Posyandu Untuk Pemantauan Status Gizi Anak Sekolah di Kecamatan Kertapati, Palembang - Syarif Husin; Ardesy Melizah Kurniati; Aryani Aziz; Medina Athiah; Fatma Syukrina; Febri Aini Nasution; Dwi Lisa Nuraini (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Teacher, Parent, and Community Health Volunteer Empowerment for Monitoring the Nutritional Status of School-Aged Children in Kertapati District. Nutritional problems among school-aged children remain a major public health challenge in Indonesia, including Kertapati District, Palembang. Limited nutrition literacy, inadequate anthropometric skills among teachers, parents, and community health volunteers (Posyandu cadres), and the lack of an integrated monitoring system contribute to delayed identification and management of nutritional problems. This community service program aimed to strengthen stakeholders' capacity and establish a sustainable school-based nutritional monitoring system. A participatory, community-based approach was implemented at SDN 195 Kertapati District. The intervention included training on nutrition and standardized anthropometric measurements, family nutrition education, and mentoring for the implementation of an integrated monitoring system. Innovations introduced were the Child Nutrition Card (Kartu Gizi Anak/KGA) as a communication tool linking teachers, parents, and Posyandu cadres, a Teacher's Pocket Guide, and digital data management using Google Sheets. Program effectiveness was evaluated using a pre-test and post-test design. The program significantly improved participants' knowledge and skills. Teachers' median test scores increased from 8.5 to 10, while parents also demonstrated meaningful improvements in nutrition knowledge. Teachers and Posyandu cadres gained competency in standardized anthropometric measurements and WHO growth chart interpretation. In addition, the School Nutrition Monitoring Team was established, and routine use of the Child Nutrition Card strengthened communication and nutritional monitoring. This multisectoral empowerment model effectively established an accurate, structured, and sustainable nutritional monitoring system for school-aged children. The model is recommended for replication in other schools and integration into local health policies.